Pengaruh Bystander Effect Dan Asimetri Informasi Terhadap Financial Statement Fraud Dengan Iman Islam Sebagai Pemoderasi - Fajrin, Farid (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to examine and determine the effect of the bystander effect and information asymmetry on financial statement fraud with Islamic faith as moderating in the Gowa Regency Regional Work Unit, South Sulawesi. This type of research is a quantitative research with a causal approach. In this study using Behavioral Decision Theory and Agency Theory. The population in this study were employees who were involved in finance, namely the finance department and the planning and reporting department as well as employees involved in the budgeting process at the Gowa Regency SKPD. The sample in this study is a saturated sample, which is sampling when all members of the population are used as samples. The number of samples obtained is 76 samples. The data used are primary data and secondary data, derived from the results of direct responses by research respondents through questionnaires and references from journals and books. The method of data collection in this study was to distribute questionnaires directly to respondents. The data analysis technique used in this research is multiple regression analysis technique and moderated regression analysis with an absolute difference value approach. The results showed that the bystander effect had a significant effect on financial statement fraud, while information asymmetry had a significant effect on financial statement fraud. In addition, the results also showed that Islamic faith moderates the bystander effect on financial statement fraud and Islamic faith cannot moderate the effect of information asymmetry on financial statement fraud. Keyword: Financial Statement Fraud, Bystander Effect, Information Asymmetry and Islamic Faith